Proceedings of the 2nd Workshop on Politics, Elections and Data 2013
DOI: 10.1145/2508436.2508438
|View full text |Cite
|
Sign up to set email alerts
|

Partisan alignments and political polarization online

Abstract: With the advent of Twitter and the ability to collect large datasets from this technology, researchers have the opportunity to analyze political participation in cross-national electoral contexts. This paper capitalizes on this capability to examine political polarization and citizen engagement during the US and French presidential campaigns. We use the Twitter Gardenhose collection to filter tweets based on keywords around a 50-day windowrespectively. From these data, we constructed partisan alignments based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
0
9
0
3
Order By: Relevance
“…On the other hand, there is considerable disagreement about the extent of partisan selectivity and ideological segregation in online political discourse. A number of studies have found no evidence of such ideological segregation (Hanna et al, 2013) or even that discussion heterogeneity does take place in online discussion platforms (Kelly, Fisher, & Smith, 2006; Lee, Choi, Kim, & Kim, 2014). Kelly et al (2006), for example, found that participants in Usenet discussion newsgroups often engage in discussion with others holding different political views.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, there is considerable disagreement about the extent of partisan selectivity and ideological segregation in online political discourse. A number of studies have found no evidence of such ideological segregation (Hanna et al, 2013) or even that discussion heterogeneity does take place in online discussion platforms (Kelly, Fisher, & Smith, 2006; Lee, Choi, Kim, & Kim, 2014). Kelly et al (2006), for example, found that participants in Usenet discussion newsgroups often engage in discussion with others holding different political views.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has repeatedly been shown that the volume of messages referring to politics rises significantly during mediated events (e.g. Burgess and Bruns 2012;Hanna et al 2013;Trilling 2014) and that users change their behavior-for instance by posting more messages containing comments on the shared experience and less containing interactions with other users (e.g. Jungherr 2014a; Trilling 2014).…”
Section: What Do Users Tweet About In Reaction To Mediatedmentioning
confidence: 99%
“…That is, individuals prefer to interact with other individuals who are similar to them, or share the same views and orientations [4][5][6]. Homophily leads to a natural polarization of societies into groups with different perspectives, that leave digital fingerprints in the online realm, and provide researchers with large-scale data sets for the study of polarization in different contexts, such as the US and French presidential elections [7], secular vs. Islamist discussions during the 2011 Egyptian revolution [8,9], or the 15M movement of 2011 in Spain [10]. Political orientation, in particular, has been shown to drive the segregation of online communication networks into separated communities [11,12].…”
mentioning
confidence: 99%